Moral-Spiritual Habituation in Community Qur'anic Learning at TPQ Anwarul Masalik Keruak - Moh. Irwan Hadi (LP2M STIT Palapa Nusantara, 2022)
Community-based Qur’anic education not only transmits recitation skills but also provides a moral ecology in which students develop manners, worship discipline, and spiritual self-control. This study aims to examine how moral-spiritual habituation is organized in Qur’anic learning at TPQ Anwarul Masalik Keruak. A descriptive qualitative approach was employed to capture the practices, meanings, and constraints of moral development within the TPQ environment. Data were collected through interviews, observation, and documentation involving the head of the TPQ and three ustaz/ustazah who were directly engaged in learning activities from February to March 2021. The data were analyzed through data reduction, thematic display, and conclusion drawing, while credibility was strengthened through source, technique, and time triangulation. The findings indicate that moral-spiritual habituation was formed through four interconnected patterns: daily manners as an entry point for akhlak al-karimah, worship routines as training for discipline and devotion, muraqabah awareness as internal moral control, and informal evaluation through repeated reminders and educator modelling. These practices were implemented through greeting routines, polite speech, cleanliness habits, Qur’anic recitation, daily prayers, exemplary stories, and advice linking behavior to accountability before Allah. The main constraints included inconsistent reinforcement outside the TPQ, differences in students’ family and peer environments, and the absence of measurable indicators for moral development. This study concludes that moral formation in TPQ requires an integrated design that connects habituation, worship practice, spiritual awareness, parental communication, and simple behavioral evaluation. Theoretically, this study contributes to the literature on moral-spiritual education in community-based Qur’anic learning, while practically, it offers implications for strengthening structured, evaluative, and collaborative moral development practices in TPQ.